Effects of COVID‐19 on communication, services, and life situation for older persons receiving municipal health and care services in Stjørdal municipality in Norway. Issue 1 (28th December 2020) - Kjerkol, Ingvild; Linset, Kristel; Westeren, Knut Ingar
Abstract: The COVID‐19 pandemic has had severe consequences for the older section of the population. In this project, we studied how COVID‐19 measures have impacted a group of older persons as users of municipal health and care services in Norway. We were specifically concerned with how communication works, in terms of the communication channels used, and what this means for the older. We also analyzed the users' experiences during the period of COVID‐19 restrictions in terms of quality of life. In addition, we looked at the municipal service providers' understanding of the situation of the older. The data collection was performed mainly in July 2020 when Norway had relatively strict COVID‐19 restrictions in relation to health and care services for older residents. Our results indicate that COVID‐19 restrictions both impaired the quality of life and security and aggravated loneliness. Regarding the older and communication, it was crucial to identify channels of communication with which the older are most comfortable. The results of this study clearly show that (a) the older had a definite preference for face‐to‐face personal communication; (b) although the older were familiar with the audio phone call and used it as a substitute for home visits, it reduced their security and quality of life; and (c) video‐based media such as smartphones, tablets, and PC were not desirable alternatives to regular voice‐based phones.